Plan de negocios de una empresa dedicada a la creación de regalos personalizados basados en pociones mágicas con dulces - Herrera Regalado, Andrés Danilo (2017)
The present business plan corresponds to the creation of a store of sweets with magic reason. In it you will be able to find products in different presentations and characteristics that generate an experience through the personalization. The first chapter will review the reason for the implementation of the work as well as its objectives that will be fulfilled throughout the present work. In the second chapter you will observe the external factors of the industry that benefit or affect and the strengths that it counts in order to combat these adversities. Some types of analysis will be realized that will give a better vision of the company in general. Then, the customer to whom the marketing efforts will be dedicated, their characteristics, tastes, preferences, acceptance of the product, ways of thinking will be analyzed. This analysis will be both qualitative and quantitative and this way you will see reflected your gains in the financial part. The marketing plan will redact the correct strategies to meet the client's needs will be proposed. It will also show the business opportunity in a clearer way with its competitive advantages which help us to survive in this market. To conclude, it will talk about the structure of the company and all its internal aspects so as to have a better knowledge of it and to know how the processes will be carried out. The financial plan will show how profitable the company is and each of the years that will take the recovery of the investment in detail.